Social media for communication and instruction in academic libraries - Joe, Jennifer, 1985-; Knight, Elisabeth, 1961- (IGI Global, 2019)
"This book examines using social media in academic libraries and in instruction, with special emphasis on assessment and evidence-based practiced. It also looks at the importance of social media in all facets of library marketing and instruction at the academic (post-secondary) level"--